AMPK controls exercise endurance, mitochondrial oxidative capacity, and skeletal muscle integrity. Issue 7 (20th March 2014) - Lantier, Louise; Fentz, Joachim; Mounier, Rémi; Leclerc, Jocelyne; Treebak, Jonas T.; Pehmøller, Christian; Sanz, Nieves; Sakakibara, Iori; Saint‐Amand, Emmanuelle; Rimbaud, Stéphanie; Maire, Pascal; Marette, André; et al.
ABSTRACT: AMP‐activated protein kinase (AMPK) is a sensor of cellular energy status that plays a central role in skeletal muscle metabolism. We used skeletal muscle‐specific AMPKα1α2 double‐knockout (mdKO) mice to provide direct genetic evidence of the physiological importance of AMPK in regulating muscle exercise capacity, mitochondrial function, and contraction‐stimulated glucose uptake. Exercise performance was significantly reduced in the mdKO mice, with a reduction in maximal force production and fatigue resistance. An increase in the proportion of myofibers with centralized nuclei was noted, as well as an elevated expression of interleukin 6 (IL‐6) mRNA, possibly consistent with mild skeletal muscle injury. Notably, we found that AMPKα1 and AMPKα2 isoforms are dispensable for contraction‐induced skeletal muscle glucose transport, except for male soleus muscle. However, the lack of skeletal muscle AMPK diminished maximal ADP‐stimulated mitochondrial respiration, showing an impairment at complex I. This effect was not accompanied by changes in mitochondrial number, indicating that AMPK regulates muscle metabolic adaptation through the regulation of muscle mitochondrial oxidative capacity and mitochondrial substrate utilization but not baseline mitochondrial muscle content. Together, these results demonstrate that skeletal muscle AMPK has an unexpected role in the regulation of mitochondrial oxidative phosphorylation that contributes to the energy demands of the exercising muscle.—Lantier, L., Fentz, J., Mounier, R., Leclerc, J., Treebak, J. T., Pehmøller, C., Sanz, N., Sakakibara, I., Saint‐Amand, E., Rimbaud, S., Maire, P., Marette, A., Ventura‐Clapier, R., Ferry, A., Wojtaszewski, J. F. P., Foretz, M., Viollet, B. AMPK controls exercise endurance, mitochondrial oxidative capacity, and skeletal muscle integrity. FASEB J . 28, 3211–3224 (2014). www.fasebj.org